Strategi Dakwah Majlis Dakwah Hamzanwadi II di Lombok - M. Gufran; Hassan Zaeni (Jurnal Komunikasi Islam, 2022)
This article discusses the da'wah strategy of Tuan Guru Lalu Gede Muhammad Zainuddin Atsani through Majlis Dakwah Hamzanwadi II in increasing adherents' understanding of the values developed by jam'iyah Nahdlatul Wathan (keNWan) as well as the Islamic teachings. By using a descriptive qualitative method, this study states that the Majlis Dakwah Hamzanwadi II uses the strategies of da'wah of tilawah, tazkiyah, dan ta’lim. Tilawah (recitation) strategy is found in the dissemination of da'wah messages through social media and during weekly sermons on Wednesdays. While tazkiyah strategy. found in preaching that focuses on aspects of soul purification. While the ta'lim strategy can be seen from da'wah activities through formal learning about hadith Arbain.